Pengaruh Pertumbuhan Penjualan, Komisaris Independen, Efisiensi Operasional, dan Kepemilikan Publik Terhadap Financial Distress - Tia Putri Permatasari; Yuli Tri Cahyono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Financial distress is defined as a condition where a company experiences difficulty in meeting its financial obligations, which can affect the company's viability. This study aims to analyze the influence of sales growth, independent commissioners, operational efficiency, and public ownership on financial distress in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2022. The sampling technique used is purposive sampling, with data taken from the annual reports and financial statements of these companies. The sample size used in this study is 153 companies. The data analysis method applied is multiple linear regression using SPSS version 25. The results of the study indicate that only the variable of operational efficiency has a significant influence on financial distress, while the variables of sales growth, independent commissioners, and public ownership do not show a significant influence on financial distress in manufacturing companies listed on the IDX during the period 2020-2022.